Functional outcome after pectoralis muscle repair. Issue 4 (July 2017) - Merlin, Gabriel; Koenig, Scott; Gross, Jordan; Edgar, Cory
Abstract : Background: The increased incidence of pectoralis major rupture in younger patients is associated with increased weightlifting in recent years, specifically the bench press. The aim of this study was to evaluate long-term outcomes in the largest series of pectoralis major repairs to date. Methods: In a single center, retrospective observational study, 68 patients underwent pectoralis major muscle repair between August 2000 and December 2010. Chart review and a subjective patient survey of outcomes were used to retrospectively assess pain, strength, stamina, overall performance, and cosmesis before and after injury, and before and after surgery. Results: Subjective questionnaires were sent to 68 patients and responses were obtained from 34 patients. On a scale of 0-6, 0 being the least desirable outcome and 6 being the most desirable outcome, the averages for pain, strength, stamina, overall performance, and cosmesis were 4.84, 4.87, 4.68, 4.45, 3.65 (compared with 1.89 after injury), respectively. The data demonstrated that pectoralis major muscle repair decreases pain and increases strength, stamina, overall performance, and cosmesis after surgery compared to directly after injury. Patients were able to bench press an average of 280 lbs before injury and 162 lbs after recovery from surgery. Complications included seven infections, which required return to the operating room. Conclusions: After complete pectoralis major rupture, it is advantageous to have a pectoralis major muscle repair by an experienced surgeon to improve comfort, strength, stamina, and overall performance.